2014
DOI: 10.1097/igc.0000000000000011
|View full text |Cite
|
Sign up to set email alerts
|

Morbidity After Pelvic Exenteration for Gynecological Malignancies: A Retrospective Multicentric Study of 230 Patients

Abstract: Although an important effort for surgeons and for patients, PE remains a therapeutic option with an acceptable complication rate and postoperative mortality. A strict selection of patients is mandatory to reach adequate surgical and oncologic outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
50
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(52 citation statements)
references
References 29 publications
0
50
0
2
Order By: Relevance
“…Some studies have demonstrated that after PE, patients 65 years and older had similar complication and survival rates to those of younger patients. 19,23,24 In our series, 2 patients were older than 65 years, both of them were 73 years old at the time of PE, one died in the postoperative period, and the other presented with no severe complications.…”
Section: Discussionmentioning
confidence: 64%
“…Some studies have demonstrated that after PE, patients 65 years and older had similar complication and survival rates to those of younger patients. 19,23,24 In our series, 2 patients were older than 65 years, both of them were 73 years old at the time of PE, one died in the postoperative period, and the other presented with no severe complications.…”
Section: Discussionmentioning
confidence: 64%
“…8 However, in this descriptive analysis, the authors did not investigate factors predicting the occurrence of morbidity. However, few researches clearly underlined that type of radiation therapy, time between radiation therapy and treatment, and other patients' constitutional variable impact on patients outcomes.…”
Section: Discussionmentioning
confidence: 95%
“…6,7 However, pelvic exenteration is associated with severe morbidity and a nonnegligible risk of mortality. 8 Moreover, it has been reported that postoperative sequelae have a profound impact on patients' quality of life. 9 Even if patient selection, enhanced perioperative care, and technical and technological improvements have reduced morbidity and mortality rate dramatically in the last years, morbidity rate still remained very high (ranging between 40% and 70%) in the more recent series.…”
mentioning
confidence: 99%
“…Recently published data suggests that the cornerstones of long-term survival after salvage (curative intent) PE (regardless of exact exenterative procedure type) are the absence of nodal and systemic metastases at preoperative evaluation and negative histopathologic margins at excision (1,(5)(6)(7)(17)(18)(19)(20)(21). Thus, the 5-year survival rate is around 50% for patients with negative margins but declines to less than 10% when the margins are positive (1,20).…”
Section: Indications and Contraindications For Pementioning
confidence: 94%
“…Factors known to adversely affect operative morbidity are the complexity of pelvic reconstruction and prior radiation therapy leading to impaired healing and immunologic response (17). In the acute postoperative setting, the most common complications seen at imaging are hematoma, abscess, lymphocele, wound dehiscence, colorectal anastomotic insufficiency (abscess, fistula, peritonitis, bowel obstruction), urinary complications (hydronephrosis, urine leak, urinoma, anastomotic breakdown), and myocutaneous flap complications (flap necrosis or abscess; donor site dehiscence, abscess, or seroma) (1).…”
Section: Complications After Pementioning
confidence: 99%